Outcomes Following Total Talus Replacement: A Systematic Review - Lindsey G. Johnson MBA; Albert T. Anastasio MD; Amanda N. Fletcher MD, MS; Stephanie Hendren MLIS, AHIP; Samuel B. Adams MD (Foot & Ankle Orthopaedics, 2022)
Category: Ankle; Hindfoot; Trauma Introduction/Purpose: Prosthetic substitution of the talus presents a unique challenge to the foot and ankle surgeon. The shear and compressive forces on the talus and its tenuous blood supply lead to high rates of avascular necrosis with possible talar collapse. The purpose of this systematic review is to evaluate whether total talus replacements (TTR) lead to improved clinical outcomes with appropriate safety metrics in patients with a history of avascular necrosis or significant trauma. Methods: Concepts of talus and arthroplasty were searched in MEDLINE (PubMed), Embase (Elsevier), CINAHL Complete (EBSCOhost), and Scopus (Elsevier) from the database's inception through November 4, 2021. Inclusion Criteria were 1) previous trauma to the talus, 2) post-traumatic or degenerative arthritis to the tibiotalar joint, 3) avascular necrosis of talus, 4) multiple failed prior interventions, 5) degenerative osteoarthritis to the tibiotalar joint, and 56) inflammatory arthropathy to tibiotalar joint. Manuscripts in non-English languages or those with concomitant total ankle arthroplasty or revision arthroplasty were excluded. All study designs were eligible according to the Journal of Bone and Joint Surgery criteria level I-IV. The modified Coleman Methodology Score was used to evaluate study quality and the Methodological Index for Non-Randomized Studies criteria was used to assess risk of bias. Results: Twenty-two studies of 191 patients (196 tali) at an average age of 50 (14-80) years were included (Figure 1a). Nineteen studies utilized third generation implants, two studies used first generation (n=9), and one study used second generation implants (n = 14) made of ceramic (n=82), cobalt chrome (n=49), or titanium (n=23) (Figure 1b). Radiographic and patient-reported outcomes are outlined in Figure 1c. The most common adverse outcome was osteosclerosis of the tibia (n=24), calcaneus (n=19), and navicular (n=5). Additionally, hindfoot varus (n=3), ankle discomfort (n = 3), decreased subtalar motion (n=7), periprosthetic fracture (n=1), calcaneal fracture (n=1), delayed wound healing (n=3), hindfoot valgus (n=1), prosthetic stem sunken into the talar neck (n=1), superficial peroneal nerve neuroma (n=1), loosening (n=2) were reported. Eight revisions were reported. Conclusion: TTR is an appealing option to maintain range of motion through the tibiotalar joint and allow for maintenance of more normal foot and ankle biomechanics. Given promising early- and mid-term outcomes, TTR is becoming more widely used in the setting of talar collapse. Still, high complication rates, especially adjacent joint osteoarthritis, may remain under-reported in the literature given inadequate long-term follow-up. Future research should aim to expand upon the indications of TTR, elucidate survivorship and complication rates, and directly compare TTR to existing forms of salvage options for advanced talar avascular necrosis.